Smart and robust composite tube columns frames for offshore sub-structure construction - Albarody, T.M.B. (Trans Tech Publications Ltd, 2014)
Offshore industry has been welcoming to composite material for its saliences. Features such as corrosion and temperature resistance, construction cost reduction, and superb fatigue performance are some of the reasons for this choice. Steel tube-encased composite is an appropriate found composite replacement for traditional offshore construction. Regardless of all its advantages, they suffer from the interfacing problem between composite and steel layers; however, magnetostrictive nanofillers are proposed to increase the integration between the layers. Therefore, current effort is discussed the vibrational behavior of the proposed robust steel tube column as well as the actuation characteristics of the magnetostrictive nanofillers in encased composite. The result reveals that, the steel tube-encased composite columns exhibit greater stiffness in compare with traditional steel tube. Furthermore, magnetostrictive nanofillers have shown higher actuation capability of vibration at seismic mode. Â© (2014) Trans Tech Publications, Switzerland.